Role of Deficient Mismatch Repair in the Personalized Management of Colorectal Cancer - Zhang, Cong-Min (Int J Environ Res Public Health, 2016)
Colorectal cancer (CRC) represents the third most common type of cancer in developed countries and one of the leading causes of cancer deaths worldwide. Personalized management of CRC has gained increasing attention since there are large inter-individual variations in the prognosis and response to drugs used to treat CRC owing to molecular heterogeneity. Approximately 15% of CRCs are caused by deficient mismatch repair (dMMR) characterized by microsatellite instability (MSI) phenotype. The present review is aimed at highlighting the role of MMR status in informing prognosis and personalized treatment of CRC including adjuvant chemotherapy, targeted therapy, and immune checkpoint inhibitor therapy to guide the individualized therapy of CRC.